Kebun Gizi dan Isi Piringku Menuju Kemandirian Pangan Desa Karangasem - Dyah Umuhanik; Luthfia Putri Oktaviana; Diyan Muslikha; Ida Priyantiningrum; Zulfa Aulia; Tasya Octaviani; Natzwa Aulia Dwi Trestya; Ersa Novalia Rahmadhani; Abdullah Habib Muhadzdzib; Dzafitri Fadhli Robbi; Abiyyu Syafiq; Naza Yaumis Ziham; Rosida Nur Syamsiyati (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2026)
The utilization of home gardens as a source of household food has become increasingly important amid limited agricultural land and rising food prices. This community service program aimed to enhance the utilization of home gardens through the Nutrition Garden (Kebun Gizi) program while improving the understanding of PKK women regarding balanced nutrition through the "My Plate" (Isi Piringku) socialization program in Karangasem Village. The methods employed included observation, educational counseling, conventional vegetable cultivation training, planting practices, and mentoring. The results demonstrated an improvement in participants' knowledge of balanced nutrition and home garden utilization, increased participation in managing the Nutrition Garden, and the use of harvested produce to meet household food needs. The program also contributed to reducing household expenditures, strengthening the role of PKK, and supporting household food self-sufficiency as well as stunting prevention efforts. Therefore, the Nutrition Garden has the potential to become a sustainable program for improving household food security and family nutrition at the village level.